Changes in echocardiographic left ventricular minor axis dimensions during exercise in patients with aortic stenosis. Issue 4 (October 1984) - Dancy, M; Leech, G; Leatham, A
Abstract : Twelve patients with aortic stenosis (gradient 62 (25) mm Hg), and six normal subjects were examined using M mode echocardiography before and during submaximal bicycle exercise. Normal subjects showed a progressive fall in the end systolic minor axis dimension of the left ventricle and a rise in end diastolic dimension, giving an increase in stroke dimension and shortening fraction of 45% and 37% respectively at peak exercise. Patients with aortic stenosis showed no consistent alteration in either end systolic or end diastolic dimension, and consequently stroke dimension was unchanged during exercise. None of the patients with an abnormal exercise response had evidence of left ventricular failure at rest, and all but one completed the exercise protocol without undue dyspnoea. Non-invasive exercise testing in patients with aortic stenosis may detect abnormalities of left heart function which are not apparent at rest. These abnormalities may provide early evidence either of severe aortic stenosis or of incipient left ventricular failure.